The intelligent social change journey: Moving into the information field of consciousness. Issue 2 (8th May 2017) - Bennet, Alex; Bennet, David; Shelley, Arthur; Bullard, Theresa; Lewis, John
Abstract : Purpose: This paper aims to share key ideas forwarded in the five-book series focused on the Intelligent Social Change Journey (ISCJ) reflecting the latest research in the Consciousness Series supported by the Mountain Quest Institute and collaborators. This review is based on five separate books released as Part I (Laying the Groundwork), Part II (Learning from the Past), Part III (Learning in the Present), Part IV (Co-Creating the Future) and Part V (Living the Future) of The Profundity and Bifurcation of Change . Design/methodology/approach: Reflecting the consilience approach taken by this in-depth research, the review of ideas provided in this paper tap into a deep array of research in knowledge and learning, with specific reference to recent neuroscience understanding that is emerging, and looks to psychology, physics, cell biology, systems and complexity, cognitive theory, social theory and spirituality for their contributions. The five books are heavily referenced (look to the larger work for these references) and, considering the individual as an intelligent complex adaptive learning system (Bennet et al., 2015b), entangle materials from science to philosophy, facts to psychology, management to poetry and words to pictures. This much shorter review can only partially represent this approach. Findings: At this point in the history of humanity ? in the midst of a conscious expansion of our human capacity and understanding ? the rules are changing. As we move away from predictable patterns susceptible to logic, we are increasingly reliant on our ?gut? instinct, an internal sense of knowing that can tap into the intuitional plane. Yet, this knowing can only serve us if we ?know? what to do with it, how to act. Development of our mental faculties is essential to acting. We are on a developmental journey of the body, mind and heart, moving from the heaviness of cause-and-effect linear extrapolations, to the fluidity of co-evolving with our environment, to the lightness of breathing our thought and feelings into reality. Grounded in development of our mental faculties, these are phase changes, each building on and expanding previous learning in our movement toward intelligent activity. Originality/value: This review lays the groundwork for the ISCJ, exploring consciousness through the lens of the cause-and-effect logic of Phase 1 (Learning from the Past), the co-evolving of Phase 2 (Learning in the Present) and the creative leap of Phase 3 (Co-Creating the Future). This research connects the expansion of consciousness to development of the human knowledge system.